A leakage-inductance-tolerant commutation strategy for isolated AC/AC converters - Nasir, Usman; Costabeber, Alessandro; Rivera, Marco; Wheeler, Pat; Clare, Jon (IEEE, 2018)
This paper proposes a generalised commutation strategy suitable for matrix-based isolated AC/AC conversion stages in Solid State Transformers for use whenever there is nonnegligible leakage inductance in the isolation transformer. The standard 4-step commutation used in matrix converters can no longer be applied when transformer leakage inductance is present, as overrated switching devices or dissipative snubbers would be necessary, reducing the attractiveness of the topologies that include matrix-based isolated AC/AC stages. A case study of a single-phase AC/AC converter has been investigated in detail to demonstrate the application of the proposed commutation method to a topology that has recently been identified as the potential building block for future multi-modular AC/AC converters for grid applications. The proposed leakage-inductance-tolerant commutation strategy is based on the definition of a current decoupling phase in the commutation sequence and only needs suitable timing of the commutation steps, without high bandwidth voltage or current measurements. Matching simulations and experimental results from a 3kW laboratory scale prototype are presented to support the effectiveness of the proposed strategy.